2014
DOI: 10.4047/jap.2014.6.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium vs. machined surfaced titanium - osteoblast and osteoclast differentiation

Abstract: PURPOSEThis study focused on in vitro cell differentiation and surface characteristics in a magnesium coated titanium surface implanted on using a plasma ion source.MATERIALS AND METHODS40 commercially made pure titanium discs were prepared to produce Ti oxide machined surface (M) and Mg-incorporated Ti oxide machined surface (MM). Surface properties were analyzed using a scanning electron microscopy (SEM). On each surface, alkaline phosphatase (ALP) activity, alizarin red S staining for mineralization of MC3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Considering the positive role of Mg in osteogenic differentiation, ECM synthesis could be started earlier in Mg containing surfaces. Positive role of Mg in Ti implants in osteogenic differentiation was reported but no information was given about the inhibition of ECM formation after certain Mg content [51,52]. Mg was shown to promote cell adhesion and differentiation via its interaction with integrins for different cell types [53,54].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Considering the positive role of Mg in osteogenic differentiation, ECM synthesis could be started earlier in Mg containing surfaces. Positive role of Mg in Ti implants in osteogenic differentiation was reported but no information was given about the inhibition of ECM formation after certain Mg content [51,52]. Mg was shown to promote cell adhesion and differentiation via its interaction with integrins for different cell types [53,54].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Previous studies have demonstrated that the effect of Mg on bone resorption plays an additional important role in bone physiology around Mg‐based implants . Kwon et al reported that Mg may speed up the bone remodeling process by activating osteoclast differentiation. Mg deficiency in animal models leads to reduced bone mass and increased skeletal fragility .…”
Section: Discussionmentioning
confidence: 99%
“…The performance of titanium implants was previously investigated with incorporated magnesium in vivo [ 298 , 299 ]. Using micro-arc oxidation, titanium surfaces with magnesium incorporation were generated and significant enhancements in osseointegration were observed, despite minimal changes in topographical parameters [ 300 , 301 ]. The magnesium-modified implants demonstrated increased resistance to removal from bone and exhibited greater bone-to-implant contact [ 302 , 303 ].…”
Section: The Use Of Magnesium In Biomaterialsmentioning
confidence: 99%